2020
DOI: 10.3390/v12111229
|View full text |Cite
|
Sign up to set email alerts
|

RNAseq of Deformed Wing Virus and Other Honey Bee-Associated Viruses in Eight Insect Taxa with or without Varroa Infestation

Abstract: The global spread of a parasitic mite (Varroa destructor) has resulted in Deformed wing virus (DWV), a previously rare pathogen, now dominating the viromes in honey bees and contributing to large-scale honey bee colony losses. DWV can be found in diverse insect taxa and has been implicated in spilling over from honey bees into associated (“apiary”) and other (“non-apiary”) insects. Here we generated next generation sequence data from 127 insect samples belonging to diverse taxa collected from Hawaiian islands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 52 publications
3
25
0
Order By: Relevance
“…as other studies using the same methodology have found a reduced DWV burden in resistant, not treated, managed populations in South Africa and Brazil [30]. [9], 2012 [29], 2012 * [17], 2015/16 [26] and 2019 (this study). 2012 and 2012 * could not be combined due to the different methodologies used.…”
Section: Figuresupporting
confidence: 76%
See 3 more Smart Citations
“…as other studies using the same methodology have found a reduced DWV burden in resistant, not treated, managed populations in South Africa and Brazil [30]. [9], 2012 [29], 2012 * [17], 2015/16 [26] and 2019 (this study). 2012 and 2012 * could not be combined due to the different methodologies used.…”
Section: Figuresupporting
confidence: 76%
“…Our results indicate a large proportion of RdRp sequences now contain those that match the DWV-B variant. This suggests that the Hawaiian Islands of Oahu and Big Island are transitioning from DWV-A to DWV-B dominance, mirroring that observed in the UK, USA, Europe, South Africa (Figure 2) [16,20,[28][29][30][31][32]. However, to confirm this would require future studies analyzing the full genome sequence of past and present samples from each island.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…We also do not specifically consider interactions between honey bees and other bees mediated via spread of shared pathogens or parasites. There is a net flow of diseases from honey bee apiaries into nearby populations of bumble bees, with possible negative spill-over to other wild bees [108][109][110][111][112]. Transmission of pathogens between species is thought to occur largely through shared flower use [113,114], thus, our analysis is likely to still identify wild bee species most at risk from being exposed to disease from honey bees [115], or the other direction, from wild bees to honey bees.…”
Section: Plos Onementioning
confidence: 99%